RANCANGAN UNDANG-UNDANG TENTANG PENGHAPUSAN KEKERASAN SEKSUAL DALAM ANALISIS FILSAFAT FEMINISME (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2021)
Increasing cases of sexual violence is caused by the primitive perspective of society which views women as sexual object. Victims of sexual violence are they difficult to get legal protection because until now there is still much legal product the have not been in favour of victims of sexual violence in particular. Therefore, a regulation that is very in favour of the voice of the victim is needed. The Bill on RUU PKS has been in the works for a long time since 2017 which aims as a legal product that can complete the existing legal vacuum and is certainly very pro-victims. In the course of its ratification, there were many pros and cons form various circles. The focus of this research is twofold, the first is to analyze the dynamics of the pros and cons to identiy the roots of the debate, the second is the urgency of RUU PKS to be ratified, seeing the increasing number of sexual violence and deemed sufficient to accomodate cases of sexual violence in giving punishment to perpetrators and is deemed sufficient in fulfilling the rights and need of victims. The study uses the library research method, using qualitative descriptive methods, namely, analyzing, describing, and related to the subject under study. In the conclusion of this study, an analysis is obtained regarding the dynamics of the pros and cons of RUU PKS and the high number of recorded cases of violence.